The Dynamics of the Earth Alms Tradition in Patat Village Waringinkurung Village, Cimanggu District, Pandeglang Regency, Banten in 2001-2018 - Lukmana, Tirta Jaya; Hadiwibowo, TB. Umar Syarif; Ribawati, Eko (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This study aims to explain the historical dynamics of the almsgiving tradition in Patat village, Waringinkurung village. This study uses a historical approach with a descriptive research type. Data collection was carried out by observation, interviews and literature studies. The theory used is symbolic interaction theory. According to Blumer, in this study the symbolic meaning contained in the Sedekah Bumi tradition is communication or interaction between humans and their gods. Then the theory of structural functionalism by Talcot Parson, is used as a reference in seeing changes in functions and relations between people in maintaining and maintaining the implementation of the earth's alms ceremony. The findings obtained from interview observations with the people of Kampung Patat are that almsgiving is a hereditary tradition carried out by the Patat community as a form of gratitude for the community, especially the farming community, for having been given sustenance and favors by Allah SWT. The earth alms tradition is routinely carried out once every seven years, but in its development several changes have occurred, for example there is a change in the series of prayers. In ancient ancestral times, prayers or worship were dedicated to Dewi Sri as the goddess of rice.